Analisis Pengaruh Kualitas Pelayanan Dan Kualitas Produk Tabungan Terhadap Kepuasan Nasabah Dengan Lokasi Sebagai Variabel Moderating( Studi Kasus Pada Nasabah Bni Syariah Di Surakarta ) - Kusworo, Octarika, BapakDrs. Atwal Arifin, Akt, M.Si (2015)
This study aimed to analyze the quality of service, product quality savings on customer satisfaction and quality of service, product quality savings on customer satisfaction with the location as moderating variable. The study involved one Islamic Bank in Surakarta. This study uses primary data derived from questionnaires to customers BNI Syariah Branch of Surakarta. Population in the study of all customers of BNI Syariah Branch of Surakarta who haveaccount savings. The research sample was determined by convenience sampling method. Testing the hypothesis in this study using multiple regression analysis. The results of regression model is: (1) variable quality of service no effect and statistically significant toward customer satisfaction, (2) variable quality savings products influence positively and statistically significant toward customer satisfaction, (3) variable quality of service with the location as a moderating effect on positive and statistically significant toward customer satisfaction, (4) the variable quality of the location as a savings product with no moderating influence and is not statistically significant to customer satisfaction.